Synthesis and electrochemical properties of a double-decker lutetium(III) phthalocyanine bearing electropolymerizable substituents on non-peripheral positions - KOCA, ATIF (ELSEVIER SCI LTD, 2014)
Double-decker lutetium(III) phthalocyanine (EDOT-LuPc2), non-peripherally functionalized with electroactive and electropolymerizable 3,4-ethylenedioxythiophene (EDOT) groups was synthesized and its electrochemical, spectroelectrochemical, and electrocolorimetric properties were studied. Totally ten redox couples, five Pc ring-based reduction, three Pc-ring based oxidation, one EDOT-based oxidation, and one electropolymerized EDOT-LuPc2 based redox couple were recorded with EDOT-LuPc2. Potential separation between the first reduction and oxidation reactions (Delta E-1/2), which reflects the SOMO-LUMO band gap of EDOT-LuPc2 decreases up to 0.28 V due to the radical feature of the one of the LuPc2 rings. Thus the first reduction reaction of the complex was recorded even at positive potentials. In addition to three Pc ring-based oxidation processes recorded before 1.0 V, EDOT-LuPc2 gives also a huge irreversible oxidation process at 1.50 V, which is easily assigned to the oxidation of EDOT moieties. Oxidation of EDOT provides electropolymerization of the complex on the working electrode and electropolymerized film of EDOT-LuPc2 illustrates extra redox waves assigned to PEDOT-LuPc2. In-situ electrocolorimetric measurements of EDOT-LuPc2 and PEDOT-LuPc2 illustrate distinct color differences between the electrogenerated anionic and cationic forms, which indicate its applications in the display technologies. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Lutetium(III) phthalocyanine; PEDOT; Electropolymerization; Electrochemistry; Sandwich complexes; Electrochromism; SANDWICH-TYPE COMPLEXES; REDOX PROPERTIES; EDOT; ELECTROCHROMISM; POLYMERIZATION; YTTRIUM; FILMS